Social media as tools for political advocacy. - Purzuelo, Danielle T. (2013.)
This study focused on the understanding of the political party lists on social media as a tool for their political advocacies. The organizational profile of the party lists, the social media they use and the benefits and drawbacks of social media for their organization were determined. This study was limited to 41 national constituency party lists based on their manifestation of intent to participate in the party-list system of representation. The study employed profiling, descriptive and quantitative design tools using mean, frequency counts and percentage for the assessment of the numerical data using the survey form. The survey form was sent either personally or as an online document on Google Docs to the respondents. In conclusion, most of the political party lists are sectoral party with which must accomodate to the different sectors they represent. However, it was found out that there were many flaws in Republic Act 7941 or the Political Party list Act of 1995. It was also concluded that political party lists do not use social media to convey their organizational goals to their public sector. They do not fully understand the role of This study focused on the understanding of the political party lists on social media as a tool for their political advocacies. The organizational profile of the party lists, the social media they use and the benefits and drawbacks of social media for their organization were determined. This study was limited to 41 national constituency party lists based on their manifestation of intent to participate in the party-list system of representation. The study employed profiling, descriptive and quantitative design tools using mean, frequency counts and percentage for the assessment of the numerical data using the survey form. The survey form was sent either personally or as an online document on Google Docs to the respondents. In conclusion, most of the political party lists are sectoral party with which must accomodate to the different sectors they represent. However, it was found out that there were many flaws in Republic Act 7941 or the Political Party list Act of 1995. It was also concluded that political party lists do not use social media to convey their organizational goals to their public sector. They do not fully understand the role of social media in relation to their organization and organizational goals.social media in relation to their organization and organizational goals.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Social media; Politiocal Advocacy